Robert Geran Landen, Oman since 1856; Disruptive Modernization in a Traditional Arab Society. Princeton University Press, Princeton, New Jersey, 1967. XV + 488 pp. - Chuaqui, Rubén (Estudios de Asia y África, 1968)
-